Prevalence of HIV infection among tuberculosis patients in Eastern India - Magna Manjareeka; Sitikantha Nanda (Elsevier, 2013)
Summary: Background: India has a high tuberculosis (TB) burden. A significant percentage of TB patients are human immunodeficiency virus (HIV) positive. As the HIV epidemic is fueling the global TB epidemic, the prevalence of the virus in TB patients is a sensitive indicator of the spread of HIV into the general population in many regions. The aim of this study was to determine the prevalence of HIV-TB co-infection among a less studied population of Eastern India. Materials and methods: A cross-sectional record analysis study covering the period from 2000 to 2011 was conducted at Central Hospital of South Eastern Railway, Garden Reach, Kolkata, India. All tuberculosis patients consenting for HIV testing were included in the study after obtaining ethical clearance from the institution. The TB diagnosis was performed using clinical examination, sputum acid-fast bacillus (AFB) smear and chest radiography. HIV-positive cases were screened using an initial HIV tridot test, followed by repetitive tests using a Micro ELISA HIV Kit for HIV 1 and HIV 2 antigen. Results: Overall, 50 (12.3%) of the consenting 406 TB patients were HIV positive. Of these 406 patients, 44% had pulmonary TB, and 56% had extrapulmonary TB (EPTB). Coughing was the most common symptom (90%), followed by fever (78%). Pleural effusion (60.7%) was the most common form observed in the EPTB cases. Conclusions: The prevalence of HIV-TB co-infection was 12.3%. Consequently, all TB patients should be assessed for HIV risk factors and counseled to undergo HIV testing. Conversely, all HIV-positive cases should be screened for TB. Keywords: Prevalence, HIV, Pulmonary tuberculosis, Extrapulmonary tuberculosis, Co-infection